Fokal epitelyal hiperplazi (Heck hastalığı): Olgu bildirisi - (:unkn) unknown (My University, 1996)
Literatürde oldukça az rastlanılan bir hastalık olarak tanımlanan Fokal Epitelyal Hiperplazi (Heck Hastalı¬ğı) saptanan bir olgudaki lezyonlar klinik ve histopato-lojik olarak incelendi. Hastanın yanak ve dudak muko¬zasında ve dilin yan kenarlarında mukoza renginde, yu¬muşak kıvamlı, farklı büyüklükte papüller saptandı. Histopatolojik incelemede çok katlı yassı epitelde akantoz ve papillamatoz vardı. Epitelin hemen alanda¬ki birkaç küçük alanda lenf osit enfiltrasyonu izlendi. Bir yıllık takip süresi boyunca lezyonlarda bir değişim saptanmadı.

A rare condition, Focal Epithelial Hyperplasia (Heck's Di¬sease) was diagnosed in a 34 year old male. The case was evaluated clinically and histopathologically. The lesions which were located on the cheek and labial mucosa and on the borders of the tongue, were in different sizes, soft and the same colour as the mucosa. Histopathologically the epithe¬lium showed acanihosis and papillamatosis. There were areas oflenfocytic infiltration just under the epithelium. During the one year petiod of observation, the lesion sho¬wed no changes essentially.
Focal epithelial hyperplasia (Heck's disease): A case report
Keywords: Diş Hekimliği